2009
DOI: 10.1016/j.pss.2009.09.012
|View full text |Cite
|
Sign up to set email alerts
|

Extremely high reflection of solar wind protons as neutral hydrogen atoms from regolith in space

Abstract: 17We report on measurements of extremely high reflection rates of solar wind 18 particles from regolith-covered lunar surfaces. Measurements by the Sub-keV 19 Atom Reflecting Analyzer (SARA) instrument on the Indian Chandrayaan-1 20 spacecraft in orbit around the Moon show that up to 20% of the impinging solar 21 wind protons are reflected from the lunar surface back to space as neutral 22 hydrogen atoms. This finding, generally applicable to regolith covered 23 -2 -atmosphereless bodies, invalidates the widel… Show more

Help me understand this report
View preprint versions

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

13
134
1

Year Published

2011
2011
2016
2016

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 147 publications
(149 citation statements)
references
References 13 publications
(16 reference statements)
13
134
1
Order By: Relevance
“…The simulations quantifiably confirm the satellite (Halekas et al 2014) findings and the theoretical predictions (Bamford et al 2012), namely that a miniature collisionless shock can be responsible for all the observations (Lin et al 1998;Huixian et al 2005;Wieser et al 2009Wieser et al , 2010Futaana et al 2010;Hashimoto et al 2010;Lue et al 2011;Wang et al 2012;Halekas et al 2014;Yokota et al 2014). Here it is confirmed that the interaction or boundary layer can form well above (i.e., kilometers rather than meters) the lunar surface (depending upon conditions) and need not be a photoelectricsheath (Garrick-Bethell et al 2011) restricted to a few meters above the surface.…”
Section: Introductionsupporting
confidence: 77%
“…The simulations quantifiably confirm the satellite (Halekas et al 2014) findings and the theoretical predictions (Bamford et al 2012), namely that a miniature collisionless shock can be responsible for all the observations (Lin et al 1998;Huixian et al 2005;Wieser et al 2009Wieser et al , 2010Futaana et al 2010;Hashimoto et al 2010;Lue et al 2011;Wang et al 2012;Halekas et al 2014;Yokota et al 2014). Here it is confirmed that the interaction or boundary layer can form well above (i.e., kilometers rather than meters) the lunar surface (depending upon conditions) and need not be a photoelectricsheath (Garrick-Bethell et al 2011) restricted to a few meters above the surface.…”
Section: Introductionsupporting
confidence: 77%
“…The magnetic field components were observed to rotate in a fashion consistent with the spacecraft passing through a region in which the solar magnetic field was being "draped" around a small magnetic obstacle or "bubble" [1]. Within the narrow barrier region is a low density cavity seen in the ion data [17]. The barrier region is of the order of kilometers across.…”
mentioning
confidence: 73%
“…At 100km Kaguya observed protons reflected back from the magnetic structures with greater energies (by factors 3 to 6) than the incident solar wind flux [13]. Chandrayaan-1 also observed back streaming protons accelerated by similar factors close to the shock surface [11,17]. These higher energy protons are accelerated by the convective electric field seen by the reflected protons in the solar wind flow [13].…”
mentioning
confidence: 99%
“…These ions may be partly neutralized and backscattered from the surface to space (up to 20% for light ions like the SW major components [see McComas et al, 2009;Wieser et al, 2009]), but a significant fraction of the incident ions, increasing with ions atomic mass number, can be implanted on the EB surface while ejecting a surface atom or molecule. Sputtering products from impacts of keV ions can have energies, peaking at few eV with a high-energy non-Maxwellian tail, up to at least several tens eV for a refractory material [Goehlich et al, 2000].…”
Section: Introductionmentioning
confidence: 99%
“…Furthermore, Chandrayaan-1 Energetic Neutrals Analyzer (CENA) was, in principle, able to measure neutral atoms of 10 eV to 3 keV [Bhardwaj et al, 2005]. This sensor observed an energetic neutral signal from the Moon surface, interpreted as the product of neutralization and backscattering of the solar wind, probably prevailing on sputtering signal at the Moon [Wieser et al, 2009]. The results and sensitivity of CENA could provide an indication for estimating an upper limit of the flux of SHEA around the Moon.…”
Section: Introductionmentioning
confidence: 99%